A preliminary review on moral challenges in tissue engineering - Ahmad Radzi, Muhammad Aa’zamuddin; Sha'ban, Munirah (Research Management Centre, International Islamic University Malaysia, 2016)
Tissue Engineering and Regenerative Medicine (henceforth TERM) research and development (R&D) is driven by substantial and growing medical needs. The ultimate goal of TERM is to reconstruct biological spare parts or living tissue graft which also known as Tissue Engineered Medical Products (henceforth TEMPs) for the human body. The emergence of this biomedical field has created numerous treatment approaches as well as prospects to manage tissue/organ loss worldwide. This advancing technology offers unique insights into its potential to customize functional human tissue/organ based on the specific needs of an individual patient. The demands for TEMPs have been increasing over time. However, other than certain technical ambiguity, its scientific progress is shrouded by several moral challenges which have yet to be addressed systematically. At present, there are only few literatures addressing the moral challenges of TERM principles and practice from the Islamic perspective. This paper attempts to bridge the gap. The discussion will try to harmonise and seek balance between the empirical aspects and the social dimensions of the technology. This paper perhaps could enlighten the stakeholders to reach answers to certain questions which may bring the best out of TERM technology.